Properties and Use of Water Activated by Plasma of Piezoelectric Direct Discharge - Konchekov, Evgeny M.; Glinushkin, Alexey P.; Kalinitchenko, Valery P.; Artem’ev, Konstantin V.; Burmistrov, Dmitry E.; Kozlov, Valery A; Kolik, Leonid V. (Frontiers in Physics, 2021)
The distilled water was exposed to a cold atmospheric plasma (CAP) generated by the piezotransformer. The treatment was carried out on a six-well plate. Exposure time was from 30 s to 10 min. The emission spectrums were obtained. Physical and chemical changes of activated water were observed for 8 days. The reactive oxygen and nitrogen species (RONS) were investigated. RONS production dependence on the exposure time and RONS lifetime in the treated liquid was determined using absorbance spectra. Quantitative assessment was made of the nitrite and nitrate concentration change over time after treatment. The medium conductivity and redox potential varied linearly depending exposure time. The pH value change correlates with nitrate anion concentration. The concentration of peroxide hydrogen increased depending on CAP water treatment duration. The RONS concentration after liquid media processing with piezoelectric direct discharge CAP is a novel result. Biogeosystem Technique provides CAP activated water agriculture synergetic effect.